INNOVATION OF SISKUEDES (VILLAGE FINANCIAL SYSTEM) IN VILLAGE FUND MANAGEMENT AS A SUPPORT FOR THE IMPLEMENTATION OF GOOD GOVERNANCE IN KALISAMPURNO VILLAGE - Rusydina Nurul Aini; Rodiyah, Isnaini (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to analyze the innovations introduced by the Village Financial System (Siskeudes) in managing village funds to support the implementation of Good Governance in Kalisampurno Village. Method: A qualitative approach with a case study method was employed, utilizing observation, interviews, and documentation, with data analysis conducted using the Miles and Huberman model, which includes data collection, reduction, presentation, and conclusion drawing. Results: The findings indicate that Siskeudes has improved the efficiency and accuracy of financial reporting, enabling village officials to prepare systematic reports that enhance transparency and accountability. However, several challenges were identified, including frequent updates to the application, difficulties in system operation, and unstable internet connectivity, all of which hinder optimal implementation. Novelty: Unlike previous studies, this research applies Rogers’ (2003) diffusion of innovation theory to highlight the adoption of Siskeudes in terms of relative advantage, compatibility, complexity, and trialability, thereby providing new insights into how technological innovations in village governance can be better understood and contextualized at the local level.